'A less unpalatable alternative': Executive leaders strategically redefining their work in primary MATs. (April 2022) - Spicksley, Kathryn
Since the election of the Coalition government in 2010, an increasing number of primary schools in England have converted to academy status. This article explores how executive leaders working in primary academies construct academy freedoms and their attitudes towards their local authorities. Interviews with four executive leaders working in two contrasting Multi-Academy Trusts were analysed using critical discourse analysis. Findings show that in these primary academies, leaders chose to discursively distance themselves from other academy schools, and instead construct themselves as continuing the best traditions of local authority support. The findings indicate that the professional identities of academy leaders, as key policy actors, have an impact on how national policy is interpreted and enacted. The discourse of these academy leaders suggests that primary academisation has led to school leaders appropriating methods of strategic redefinition, to navigate the new post-2010 education landscape and construct new professional identities.